Dendritic cell-mediated delivery of doxorubicin-polyglycerol-nanodiamond composites elicits enhanced anti-cancer immune response in glioblastoma. (October 2018) - Li, Tong-Fei; Li, Ke; Zhang, Quan; Wang, Chao; Yue, Yuan; Chen, Zhuo; Yuan, Shen-Jun; Liu, Xin; Wen, Yu; Han, Min; Komatsu, Naoki; Xu, Yong-Hong; et al.
Abstract: Glioblastoma (GBM) is the deadliest and most common type of primary brain tumor in adults with a grim prognosis despite multimodal treatments. Dendritic cell (DC)-based immunotherapy has emerged as a promising therapeutic modality for GBM, whose efficacy is nonetheless fundamentally undermined by GBM-induced immunosuppression. Inducing emission of damage associated molecular patterns (DAMPs) is a highly effective strategy to subvert tumor-associated immunosuppression. The present work was carried out to explore the idea of subverting the GBM immunosuppressive microenvironment through DC-mediated delivery of doxorubicin-polyglycerol-nanodiamond composites (Nano-DOX), a potent DAMPs inducer demonstrated by our previous study, and thereby eliciting enhanced DC-driven anti-GBM immune response. In the in-vitro work on human cell models, Nano-DOX-loaded DC were shown to be functionally viable and release cargo drug to co-cultured GBM cells (GC). Nano-DOX-treated GC displayed not only profuse DAMPs emission but also antigen release. Enhanced activation and acquisition and presentation of GC-derived antigen were then demonstrated in DC in co-culture with GC and Nano-DOX. Consistently, co-culture with GC and Nano-DOX also activated mouse bone marrow-derived DC (mDC) which in turn stimulated mouse spleen-derived lymphocytes which ultimately suppressed co-cultured GC. Next, athymic mice bearing orthotopic human GBM xenografts were intravenously injected with Nano-DOX-loaded mDC and, 48 h later, spleen-derived lymphocytes. The presence of Nano-DOX, DAMPs emission and enhanced infiltration and activation of mDC and lymphocytes were detected in the GBM xenografts. Taken together, our results demonstrate the efficacy of DC-mediated delivery of Nano-DOX to stimulate GC immunogenicity and elicit anti-cancer immune response in the GBM. By this work, we present a novel approach with great application potential to subverting the GBM immunosuppressive microenvironment and to anti-GBM immunotherapy. Investigation has also been conducted probing the mechanisms by which Nano-DOX stimulates GC immunogenicity, which is described in a follow-up paper. Graphical abstract: Image 1